The oxidoreductases POR and CYB5R1 catalyze lipid peroxidation to execute ferroptosis. (4th March 2021) - Ai, Youwei; Yan, Bo; Wang, Xiaodong
ABSTRACT: Our recent study showed that two oxidoreductases – NADPH-cytochrome P450 reductase (POR) and NADH-cytochrome b5 reductase (CYB5R1) – transfer electrons to oxygen to generate hydrogen peroxide (H2 O2 ). H2 O2 then reacts with ferrous iron, generating hydroxyl radicals that cause peroxidation of polyunsaturated-fatty-acid chains of membrane phospholipids, resulting in plasma membrane rupture and ferroptosis.